Relationship of serum ferritin level with prognosis in maintenance hemodialysis patients - WANG Ming-li; CHEN De-zheng (Linchuang shenzangbing zazhi)
Objective To explore the relationship of serum ferritin(SF) level with prognosis in maintenance hemodialysis patients.Methods From June 2011 to December 2012, 180 patients with end-stage renal diseases(ESRD) who underwent maintenance hemodialysis in the Department of Nephrology of Jianyang People’s Hospital were selected as the subjects. These patients were followed up until December 31, 2017. Dialysis related indicators and outcome indicators were recorded. The main endpoint event was death. Cumulative survival rate was calculated with a non-parametric product estimation method, the Kaplan-Meier method. Single-variate and multivariate COX proportional hazard models were adopted to analyze the independent hazard factors influencing prognosis of maintenance hemodialysis patients. Results The one-year, two-year, three-year and five-year cumulative survival rates of the high SF group and low SF group were 78.57%, 69.05%, 57.14%, 42.86% and 89.86%, 82.61%, 73.91% and 60.15%, respectively. There was a significant difference in survival rate between the two groups by Log-rank test showed difference of statistical significance in the survival rate between two groups(P<0.05). Multivariate COX regression analysis indicated that high SF level was an independent hazard factor for mortality in maintenance hemodialysis patients(P<0.05). The mortality rates of cardiovascular disease and infection in the high SF group was higher than that those in the low SF group(P<0.05). Conclusions The survival rate of hemodialysis patients with high SF level is relatively low. High SF level is an independent hazard factor for mortality in maintenance hemodialysis patients.